KEADAAN SOSIAL EKONOMI KELUARGA PETANI SAWAH TADAH HUJAN - Dila Afdila; Sudarmi Sudarmi; Edy Haryono (JPG (Jurnal Penelitian Geografi), 2013)
The aim of this research was to find out the social economy condition of rainwater farming in Fajar Baru Village, Jati Agung sub district of southern Lampung year of 2012. The focus of this study were age, education level, number of children and other dependents, extensive land holdings, the type of side jobs, income, and level of minimum rate of the family. The researcher used descriptive method. The population of this research were 185 family heads, and were taken 20% as samples (37 family heads). For data collection, the researcher used observation, interview, questionnaire, and documentation. Data analysis with tabulations and percentages were used as the basis for the interpretation and description in making of this research report. The results showed that: (1) 94,6% of family heads’ age were productive (20-64 years), (2) 91,8% of respondents had basic education, (3) 72,9% of respondents had more than 5 dependants and 67.5% of respondents had more than 3 children, (4) 35,2% of the land area of the farmers’ ownership were small/narrow ( 0.25-0.49 ha), (5) 56.7% of respondents had side jobs as building laborers (6) 70.3% of respondents had under income averaging Rp 14.794.554 per year), and 81.1% of respondents have fulfilled level of minimum rate of the family. Keywords: social economy condition, farmers of rainwater farming